Gastrodia dayaoshanensis (Orchidaceae: Gastrodieae), a new species from Guangxi, China - Li, Xiong; Huang, Yu-Song; Sun, Zhuo; Zhu, Lu; Xie, Yong; Liu, Kun; Qin, Ying; Liu, Ang (Phytotaxa, 2025)
Gastrodia dayaoshanensis, a new species from Dayaoshan National Nature Reserve, Guangxi, China is described and illustrated. The new species is morphologically similar to G. peichatieniana, G. longistyla and G. menghaiensis, but can be distinguished from G. peichatieniana mainly by its brown flowers, sepals and petals entire or with a few teeth at margin, united portion of lip with 2 ridges, and from G. longistyla mainly by its wider free portions of sepals, united portion of lip with 2 ridges, stigma without appendage, and from G. menghaiensis mainly by its brown and straight perianth tube, sepals and petals entire or with a few teeth at margin, united portion of lip without calli. A detailed taxonomical description along with photoplates and a comparison with the allied species have been provided to aid in easy identification.